(untitled) (Bangladesh Journal of Medical Science, 2017)
Social media connect people by sharing text, photos, audio and videos among themselves. Medical professional and patients also communicate through social media; however, issues of privacy and confidentiality of medical professions in regards to medical and health care decisions contradict with the openness of the usage of social media. Member of the medical profession can use social media but need to abide by the code of conduct of medical ethics in order to render the best possible services. This paper emphasizes on the needs of inclusion of social media usage in future health care providers curriculum by the higher educational institutions in order to aware of the ethical and professional aspect. Bangladesh Journal of Medical Science Vol.16(4) 2017 p.606-609